Diseño del Sistema de Control Interno para el Comercial T.V. Electrodomésticos de la Ciudad de Loja - Sánchez Armijos, Stefany Gabriela (2017)
The degree work is related to the Design of the Internal Control System for a private company domiciled in the city of Loja-Ecuador; Company dedicated to the sale of high quality appliances for all types of customers. The first specific objective that was proposed to the commercial was to draw up internal control procedures with a financial approach that would safeguard the resources, as well as verify the accuracy and veracity of the financial and administrative information. This objective was fulfilled with an interview with the manager and accountant, to know in general form if internal control is applied, if it complies with current regulations and management to obtain excellent profitability. For the fulfilment of the second objective, that is to propose procedures of administrative and financial order that guarantee the achievement of the business objectives. The Design of the Internal Control System was proposed, the same that will help the development of commercial activities. Finally, we present the conclusions and recommendations focused on giving guidance to the manager for the improvement of the entity